Analisis Yuridis Terhadap Proses Penyidikan Dalam Penanggulangan Jaringan Peredaran Narkotika Yang Dikendalikan Narapidana Di Lembaga Pemasyarakatan - Talia Nava Vanessa; Andi Bustamin Daeng Kunu; Budi Arta Pradana Nongtji (Journal Law and Government, 2026)
Illicit narcotics trafficking in Indonesia has evolved into an organized, transnational crime that threatens the social order and violates the provisions of Law Number 35 of 2009 concerning Narcotics. Ironically, this illegal activity is not only prevalent in the community but has also transformed into a complex socio-legal phenomenon within correctional institutions (prisons). This situation raises issues regarding the effectiveness of investigative processes in uncovering and combating narcotics trafficking networks controlled from inside the prison. Therefore, this study aims to analyze the implementation of the investigative process and identify the factors enabling inmates to continue controlling narcotics trafficking. An empirical research method with a field-based approach was employed at the Class II A Correctional Institution in Palu City, integrating primary data sources obtained through observation and interviews with secondary data derived from the study of legislative documents. The research findings indicate that while the investigative process is implemented in accordance with statutory regulations, it faces various practical obstacles, such as the misuse of communication devices and the involvement of certain individuals. These factors hinder efforts to effectively combat inmate-controlled narcotics trafficking networks. Consequently, there is a need for enhanced supervision, strengthened coordination among law enforcement agencies, and stricter law enforcement to dismantle narcotics trafficking networks operating from within correctional institutions.